Prospects for the conservation of Fraxinus sogdiana through micropropagation and slow growth storage approaches - AIZHAN RAKHIMZHANOVA; BALNUR KALI; NURBEK ZHUMABAY; DILNUR TUSSIPKAN; SHUGA MANABAYEVA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Rakhimzhanova A, Kali B, Zhumabay N, Tussipkan D, Manabayeva S. 2026. Prospects for the conservation of Fraxinus sogdiana through micropropagation and slow growth storage approaches. Biodiversitas 27 (4): d270421. https://doi.org/10.13057/biodiv/d270421. Fraxinus sogdiana is a rare species listed in the Red Book of Kazakhstan, highlighting the urgent need for effective conservation strategies. This study aims to develop an effective micropropagation protocol, slow growth storage approaches and analyze phylogenetic relationships by comparing F. sogdiana from Kazakhstan with species from the NCBI database. The results of this study demonstrate that the DKW medium outperformed the MS medium in promoting shoot development. A DKW-based MP-V medium supplemented with 1.0 mg/L BAP, 0.1 mg/L NAA, and 0.5 mg/L gibberellic acid was found to be optimal for shoot proliferation. This resulted in maximum shoot lengths of 11.54 cm and an average of seven shoots per explant. High concentrations of BAP alone inhibited shoot formation. In slow-growth storage experiments, the addition of 0.5 mg/L CCC provided the best balance between shoot survival and growth retardation. In contrast, mannitol and ABA suppressed shoot development and decreased the survival rate. Based on their ITS patterns, five main groups were identified according to the sections of genus Fraxinus, including Fraxinus, Sciadanthus, Melioides, Pauciflorae, and Ornus. Notably, seven sequences from the species Fraxinus angustifolia, Fraxinus obliqua, Fraxinus sogdiana, and Fraxinus turkestanika, previously considered synonyms, were grouped together with strong bootstrap support. The results of the matK and rbcL gene patterns did not correspond to clearly defined taxonomic groups according to sections. The main finding of the matK gene region analysis was that the populations from Kazakhstan and China were closely related, as indicated by a high bootstrap value. These findings provide an effective protocol for preserving the genetic resources of F. sogdiana, as well as a phylogenetic framework to support future biotechnological and molecular studies.